Pengaruh Suhu dan Lama Pelayuan Terhadap Karakteristik Teh Herbal Daun Kenikir (Cosmos caudatus Kunth.) - Aprilia, Maria; Wisaniyasa, Ni Wayan; Suter, I Ketut (Jurnal Ilmu dan Teknologi Pangan (ITEPA); Vol 9 No 2 (2020): Jurnal ITEPA, 2020)
This research aimed was to determine the effect of temperature and duration of withering on the characteristics of herbal tea of kenikir leaves (Cosmos caudatus Kunth.) and to know the right temperature and duration of withering time to get the best characteristics of herbal tea. The experimental design used was Completely Randomized Design with two factors which were withering temperature (70oC, 80OC, and 90oC) and withering duration (1, 2, and 3 minutes). All of the treatment was repeated two times to obtain 18 units of experiments. The data obtained were analyzed by variance and if the treatment had a significant effect followed by The Duncan Multiple Range Test. The results showed that interaction of temperature and withering time had a very significant effect on moisture content, total phenolics, total flavonoids, antioxidant activity, and color (scoring test). The results showed that interaction 90oC of withering temperature during 2 minutes was the best treatment to produce kenikir leaves herbal tea with the moisture content 6,76% b/b, extract content 32,89%, vitamin C 3,35 mg /g total phenolics 79,26 mg GAE/g, total flavonoids 161,01 mg QE/g and antioxidant activity 74,29% with IC50 valued 24,409 ppm. The brew of kenikir leaves herbal tea had a rather typical aroma of kenikir leaf and liked, yellow greenness color and liked, rather bitter taste and usual as well as with overall acceptance. Keywords : characteristics of herbal tea, kenikir leaves, withering temperature, withering duration.